2003
DOI: 10.1021/jf034139f
|View full text |Cite
|
Sign up to set email alerts
|

Defining the Ascorbic Acid Crossover from Anti-Oxidant to Pro-Oxidant in A Model Wine Matrix Containing (+)-Catechin

Abstract: An examination of the ascorbic acid-induced oxidation of (+)-catechin was carried out. Using varying concentrations of ascorbic acid in a model white winebase, it was observed that there are at least two distinct steps in its oxidation process. The first step involves the formation of species that absorb in the visible region of the spectrum, while the second step generates species of less or no absorbance in the visible region. The first step reaches an absorbance maximum when ascorbic acid is completely oxid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
45
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(52 citation statements)
references
References 24 publications
6
45
1
Order By: Relevance
“…iron and copper . Bradshaw et al . found that the browning induction effect of ASC on (+)‐catechin model solutions (stored in enhanced oxidative conditions at 45 °C) became evident after a lag period that ranged from 1 to 7 days, depending on the ASC concentration.…”
Section: Resultsmentioning
confidence: 64%
See 1 more Smart Citation
“…iron and copper . Bradshaw et al . found that the browning induction effect of ASC on (+)‐catechin model solutions (stored in enhanced oxidative conditions at 45 °C) became evident after a lag period that ranged from 1 to 7 days, depending on the ASC concentration.…”
Section: Resultsmentioning
confidence: 64%
“…GSH offered a certain amount of color protection, probably as a consequence of its well‐known ability to scavenge quinones . ASC also produced good color protection, and no evidence of the so‐called ‘crossover’ effect was observed over the entire 29 days of storage. As known, the ‘crossover’ effect is connected with the ability of ASC to act as both antioxidant and pro‐oxidant, depending on the level of available ASC and the ratio of ASC to catalytic metal ions, i.e.…”
Section: Resultsmentioning
confidence: 99%
“…On the contrary, recent studies have shown the increased production of phenolic pigments in model wine systems from ascorbic acid and (+)-catechin and demonstrated that a degradation product emanating from ascorbic acid was able to react with (+)-catechin and to form colored xanthylium cations (Barril et al, 2009;Barril, Clark, & Scollary, 2008;Bradshaw, Prenzler, & Scollary, 2001;Bradshaw, Prenzler, Scollary, & Cheynier, 2003). Furthermore, the stereochemical influence of ascorbic acid and erythorbic acid on the oxidation processes in a model wine system was studied and xanthylium cation pigments were identified as the major contributor to color development.…”
Section: Other Antioxidants In Wines: Sulfur Dioxide and Ascorbic Acidmentioning
confidence: 98%
“…Also, sulphur dioxide does not seem to minimise this browning effect (Peng et al, 1998;Bradshaw et al, 2001). When Bradshaw et al (2001Bradshaw et al ( & 2003 oxidised ascorbic acid alone, two phases were observed. The first was the complete oxidation of ascorbic acid, with species being generated that absorb in the visible spectra.…”
Section: Oxygen In Must and Winementioning
confidence: 99%